Chattering suppression of the sliding mode observer for marine electric propulsion motor based on piecewise power function - Li, Xiangfeng; Zhan, Shengqiang; Guo, Fang; Zhuang, Zidan; Zhang, Huitao; Liao, Hui; Qu, Lili (Frontiers in Energy Research, 2022)
The sliding mode observer (SMO) based sensorless control is essentially a discontinuous switching control algorithm, therefore there are large speed or torque chattering in permanent magnet synchronous motor (PMSM) with existing SMO based control methods. In order to well solve this essential problem, an algorithm based on an improved SMO is proposed. In detail, the piecewise power function approach is used to replace the traditional ones, i.e., sgn function or sigmoid function approach. Simulation verifications are conducted to validate the effectiveness of the proposed observer, and simulation results show that the improved SMO algorithm has obvious advantages in the stability of three-phase current, i.e., it improves the estimation accuracy of motor position and speed, and the dynamic response to various loads. For further verifications, the proposed SMO algorithm is implemented and verified in a marine electric propulsion motor with a DSP chip of TMS320F28377D. Experimental results well validate that the proposed SMO algorithm has high control accuracy and fewer fluctuations, which are all vital in marine engineering.